Properties of the running coupling constant of strong interaction at low energies - V. A. Babenko; N. M. Petrov (Ядерна фізика та енергетика)
Quantum chromodynamics (QCD) running coupling constant and its dependence on the energy scale renormalization parameter are studied in the energy range of μ ≲ 25 GeV based on the five-loop calculations according to QCD renormalization group equation. Position of the Landau pole of the dependence (QCD scale parameter ) is calculated in the five-loop order for the first time. Energy dependence of the running coupling constant in the given energy range is very well described by the proposed simple one-pole formula.